Farmers' agrochemicals usage and willingness to adopt organic inputs: Watermelon farming in Bangladesh - Md. Najmol Hoque; Sourav Mohan Saha; Shahin Imran; Afsana Hannan; Md. Mahdi Hasan Seen; Syed Sakib Thamid; Fatema Tuz-zohra (Environmental Challenges, 2022)
Extensive and improper use of agrochemicals by the farmers is disrupting environmental conditions and endangering human health. The use of organic inputs is the most reasonable solution for ecological sustainability. This study assessed the use of various agrochemicals in watermelon farming in the southern region of Bangladesh and evaluated farmers' willingness to adopt organic inputs. Primary data were collected from 120 watermelon farmers of Khulna district. Adoption Quotient Index was employed to assess farmers' usage of agrochemicals, and a Tobit model was used to determine the factors influencing their usage. In addition, determinants of farmers' willingness to adopt organic inputs were identified through logistic regression. Results revealed that no farmers received any training on the use of agrochemicals. They used overdoses of different fertilizers and crop protective chemicals. The farmers' educational level, farming experience, and extension positively affected the use of agrochemicals, whereas farm size had a negative effect. About 65.8% of the watermelon farmers were willing to adopt organic inputs, and anticipated loss of production is the primary cause for unwillingness in adoption. Farmers' educational level, watermelon farming experience, and training positively influenced their willingness, while annual income had a negative impact. This study suggests conducting proper economic evaluation of watermelon production considering environmental and social costs, educating and providing training to the farmers on appropriate agrochemicals usage and organic inputs for sustainable watermelon production.